Penggunaan Variasi Bahasa “Slang Language” Pada Platform Tiktok Untuk Generasi Z: Kajian Sosiolinguistik - Dewi, Ni Putu Juliani Lestari (Scholars: Jurnal Sosial Humaniora dan Pendidikan, 2024)
Research on the Use of "Slang Language" Variations on the Tiktok Platform for Generation Z: Sociolinguistic Studies certainly discusses the use of slang language variations on the Tik Tok platform or social media. The problem formulation in this research consists of types of slang language variations, the use of slang language variations and their meanings. The aim of this research is to describe the use of slang variations on the Tik Tok platform or social media and their meanings. The research method in this study is qualitative descriptive research which aims to provide symptoms, facts or events systematically and accurately. There are approximately 60 forms of slang variations used by generation z/teenagers on the Tik Tok platform or social media. Of the 60 data on language variations, 23 data are mispronunciations, 29 data are abbreviations, 3 data are shortened forms and 5 data are interjections. Variations of slang with data in the form of abbreviations are the most widely used by generation z/teenagers because the form is more practical and easy to apply and memorize. Keywords: slang, language variations, tik tok, generation z, sociolinguistics